Brain Death Scintigraphy and Pathology Results in a Rat Model - Guzel, Yunus; Koc, Zehra Pinar; Mitil, Huseyin Aydin; Kom, Mustafa; Ozer, A. Belin; Ozercan, H. Ibrahim; Balci, Tansel Ansal (Baskent Univ, 2014)
Objectives: Brain scintigraphy with Tc-99m-labeled diethylenetriaminopenta-acetic acid is a sensitive diagnostic method showing loss of cerebral blood flow that occurs after brain death. Cerebral blood flow can be quantitatively estimated by this method. The aim of this study was to compare histopathologic changes occurring with the decrease of cerebral blood flow (as shown by Tc-99m-labeled diethylenetriaminopenta-acetic acid brain death scintigraphy) after brain death in an experimental model. Materials and Methods: The study included examination of cerebral blood flow by Tc-99m-labeled diethylenetriaminopenta-acetic acid brain scintigraphy in the 20 rats, 1 day before brain death, after producing brain death in 11 surviving rats. Tc-99m-labeled diethylenetriaminopenta-acetic acid brain scintigraphy was performed under intubation and monitored. The Mann-Whitney U test was performed to compare groups (scintigraphic quantification results before and after brain death). Results: In the time activity curves generated from the analysis of the scintigraphies, decreases in counts in the brain death group were obtained in the arterial phase (P < .01). Decreases of the cerebral blood flow between the first and the sixth minutes were statistically significant (P < .05). Common principal histopathologic changes of the brain death (ie, autolysis and color loss in the nerve cells, diffuse edema, petechial hemorrhage in the brain tissues) were observed in all subjects. Conclusions: Quantitative findings of the brain scintigraphy by Tc-99m-labeled diethylenetriaminopenta-acetic acid was related with the histopathologic findings seen during the early brain death, with significant decreases of the cerebral blood flow. Quantification of Tc-99m-labeled diethylenetriaminopenta-acetic acid brain death scintigraphy as an easier and less-expensive scintigraphic method of cerebral blood flow might indicate a definite diagnosis of brain death and thus, potential donors can be determined earlier, leading to increased transplant rates.
Keywords: Brain death; Tc-99m DTPA; Scintigraphy; Cerebral blood flow; Histopathologic findings